2016
DOI: 10.1016/j.jvsv.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Improving the retrieval rate of inferior vena cava filters with a multidisciplinary team approach

Abstract: Objective The option to retrieve inferior vena cava (IVC) filters has resulted in an increase in the utilization of these devices as stopgap measures in patients with relative contraindications to anticoagulation. These retrievable IVC filters, however, are often not retrieved and become permanent. Recent data from our institution confirmed a historically low retrieval rate. Therefore, we hypothesized that the implementation of a new IVC filter retrieval protocol would increase the retrieval rate of appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Complications associated with permanent IVC filters, including IVC thrombosis, spurred the development of retrievable IVC filters in the 1990s but these devices were not approved in the United States until 2004 . Thus, the IVC filter in our patient was unlikely to have been designed for retrieval.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Complications associated with permanent IVC filters, including IVC thrombosis, spurred the development of retrievable IVC filters in the 1990s but these devices were not approved in the United States until 2004 . Thus, the IVC filter in our patient was unlikely to have been designed for retrieval.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the IVC filter in our patient was unlikely to have been designed for retrieval. Interestingly, a recent study found that despite a 200% increase the use of these “temporary” IVC filters, the actual retrieval rates remain quite low (12%–45%) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In three studies, Klinken et al [5], Inagaki et al [6], and Lynch [7] describe prospectively tracking patients who received IVC filters in a database. In all of these studies, an IR team assumed responsibility for follow-up of patients, and Inagaki et al described the creation of a multidisciplinary task force.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several studies demonstrated the effectiveness of multidisciplinary filter retrieval protocols, which utilize the input of a number of different specialists to provide care. [1][2][3][4] One such study found that IVC filter retrieval tripled over the course of five years after implementation of post-procedure care and patient education, maintenance of an IVC filter database, post-discharge patient outreach, and intervention by a thrombosis specialist to assess the ongoing need for the filter and to coordinate retrieval.4 Similarly, other academic medical centers independently enacted multidisciplinary approaches that improved their retrieval rates by augmenting patient education, standardizing post-procedure care, and designating coordinators for post-procedure follow-up and filter retrieval. 1,3,10 The University of Pittsburgh Medical Center utilized a multidisciplinary approach that emphasized educating trauma providers, rather than patients, on the indications for retrievable IVC filter insertion and retrieval.…”
Section: Clinical Contextmentioning
confidence: 99%